Evaluation of Sustainability Indicators in Smart Cities for India Using MCDM Approach. (December 2017) - Anand, Atul; Winfred Rufuss, D. Dsilva; Rajkumar, V.; Suganthi, L.
Abstract: A smart city is defined as a sustainable and efficient city center providing high quality of life by optimally using its resources. Managing its resources especially energy is a very crucial factor owing to the complexity of various interlinked parameters. In this paper, the importance of various criteria for sustainability in a smart city are determined using fuzzy and fuzzy-AHP method. The sustainability indicators for designing a smart city in a developing country has been identified. DEA:AR-CCR model is adopted to determine the relative efficiency of each of the sustainability indicators for a smart city in the context of input and output criteria. The decomposition efficiency measures clearly highlight which sustainability indicator the country needs to focus based on the importance of the input criteria to achieve the desired outputs. It was found policy makers and administrators have to design policies for economic development (0.85) and energy (0.82) for achieving economic prosperity of the nation.